Center-Pivot-Irrigated Grain Sorghum Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2004)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated grain sorghum production in western Kansas.
MF582_2004_10
Keywords: MF582; Economics; Crops; MF